KEKUASAAN VLADIMIR PUTIN DALAM PERKEMBANGAN DEMOKRASI FEDERASI RUSIA - Suwanti, Ika (Transformasi, 2015)
This thesis discusses about Vladimir Putin powers in the developing Russia federation development. Empire Russian Empire Kingdom led by the Tsar finally managed undermined through the Bolshevik Revolution leader Vladimir Lenin in 1991 IIych. Lenin then form a new country which he named the Soviet Union ( USSR ) . The dissatisfaction of the people will be a model of leadership that the Soviet Union no less authoritarian with the Tsar made the Soviet Union finally had to stop as a nation . Russian Federation was born as the successor state more democratic . Boris Yeltin who became the first president of Russia in the end failed to run his administration .Replaced by Vladimir Putin who then managed to overcome the complexity of the problems being experienced by Russia in the transition period. According from Miles and Huberman anlisist, which includes context evaluation , input evaluation , prosses evaluation and product evaluation. Data collection techniques used is to study literature by collecting data through books , journals , newspapers , and trusted sites on the internet. And the coclusion is what the global picture by the power of Vladimir Putin on Transition Democracy can developing the countryside. Keywords: power, Vladimir Putin, government, democracy